Hubungan Kepercayaan Diri dan Kecemasan Bertanding dengan Mental Toughness Pemain Futsal Madrasah - Anugrah, Rendi Diski; Kesumah, Dadang Warta Chanra Wira; Muliyani, Sri Erny; Irmansyah, Johan; Wasa, Carolus (Discourse of Physical Education, 2026)
School and madrasah futsal players often face match pressure, spectator reactions, and performance demands that may influence their mental toughness. This study aimed to examine the relationship of self-confidence and competitive anxiety with mental toughness among MA NW Gonjong futsal players. A quantitative correlational approach was used, involving 20 players selected through total sampling. The instruments consisted of self-confidence, competitive anxiety, and mental toughness scales. Data were analyzed using descriptive statistics, assumption tests, correlation, and multiple regression. The results showed that self-confidence and competitive anxiety simultaneously had a significant relationship with mental toughness (F = 4.457; p = 0.028), with the model contributing 34.4%. However, partial tests showed that self-confidence (p = 0.068) and competitive anxiety (p = 0.718) were not significant predictors. In conclusion, the combination of both variables is related to mental toughness, but their partial relationships were not statistically strong.